2009
DOI: 10.1002/jor.20854
|View full text |Cite
|
Sign up to set email alerts
|

No efficacy of silver bone cement in the prevention of methicillin‐sensitive Staphylococcal infections in a rabbit contaminated implant bed model

Abstract: Data from literature showed that a new type of metallic silver PMMA cement had good results in infection prophylaxis. This study investigated the in vivo efficacy of silver cement in the prevention of methicillin-sensitive Staphylococcal infections, compared to plain and tobramycin-containing cement. In 48 rabbits, 0.6% silver, 1% silver, plain, or tobramycin PMMA cement was injected into the femoral medullary canal after contamination with 10 5 , 10 6 , or 10 7 colony forming units (CFU) Staphylococcus aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The average percentage reduction changed from 38.6% to 80.38% and 28% to 86.11% ( p < 0.05) for E. coli and S. aureus , respectiovely (Figure A, B). These results are improvements compared to recent reports on antibiotics (Neut et al ., ) and silver (Moojen et al ., ) injected bone cements or silver‐containing polymeric scaffolds (Olgun et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The average percentage reduction changed from 38.6% to 80.38% and 28% to 86.11% ( p < 0.05) for E. coli and S. aureus , respectiovely (Figure A, B). These results are improvements compared to recent reports on antibiotics (Neut et al ., ) and silver (Moojen et al ., ) injected bone cements or silver‐containing polymeric scaffolds (Olgun et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…However, in vivo studies of PMMA/1 wt% n-Ags in rabbit models showed no antimicrobial effect against methicillin-sensitive S. aureus in all 12 rabbits, whereas PMMA incorporated with tobramycin lead to infection in only two out of 12 rabbits [94]. These results suggest that although 1 wt% n-Ags might be effective in preventing bacterial growth on the surface of PMMA itself, it is not effective in inhibiting the growth of bacteria in the surrounding tissue [94]; therefore, more investigation into the optimal n-Ag size and concentration may be required in order to obtain optimum antibacterial properties and minimal cytotoxicity. Chitosan nanoparticles have also been shown to introduce antibacterial properties into PMMA [91].…”
Section: Antibacterial Propertiesmentioning
confidence: 83%
“…There are many reports of an effect of silver-containing materials when tested in vitro, but in most cases the in vivo effects are limited or absent (32,58,74,81). One exception is the investigation by Kumar and Munstedt (47), who reported antibacterial effect in vivo with polymers releasing silver in its oxidized form.…”
Section: Methodsmentioning
confidence: 92%